Persuasive Communication of Rumah Baca Komunitas (RBK) in Increasing Children's Reading Interest in Kanoman 2021/2022 - Trias Desri Asmarita; Sovia Sitta Sari (Jogjakarta Communication Conference (JCC), 2023)
This study seeks to analyze persuasive communication carried out by the Rumah Baca Komunitas (RBK) to children to increase their interest in reading. The purpose of this research is to describe the persuasive communication carried out by the Rumah Baca Komunitas (RBK) to children in Kanoman, so that children's interest in reading can increase. This research is descriptive qualitative research. Sources of data obtained through observation and in-depth interviews. The informants in this study were the founders and activists of the Rumah Baca Komunitas (RBK) and teachers in Kanoman. This research was analyzed using persuasive communication techniques and methods according to Effendy and Gary A. Yukl. Based on the research, it was found that each activist used different persuasive techniques and methods to increase children's interest in reading. Mia uses pay of techniques, ingratiation techniques and coalition techniques and methods at different times. Hasyim uses ingratiation techniques. Meanwhile, Faiz uses pay of technique and coalition techniques. The response given by the children was quite good, such as the focus on playing the children was distracted and immediately looking for reading books, there were children's visiting activities, and the enthusiasm of the children to take part in practical activities held by the Rumah Baca Komunitas (RBK). The obstacles encountered came from the lack of parental support, time between activists and language.